The structure and repertoire of small interfering RNAs in Leishmania (Viannia) braziliensis reveal diversification in the trypanosomatid RNAi pathway. Issue 3 (26th December 2012) - Atayde, Vanessa D.; Shi, Huafang; Franklin, Joseph B.; Carriero, Nicholas; Notton, Timothy; Lye, Lon‐Fye; Owens, Katherine; Beverley, Stephen M.; Tschudi, Christian; Ullu, Elisabetta
Summary Among trypanosomatid protozoa the mechanism of RNA interference (RNAi) has been investigated in Trypanosoma brucei and to a lesser extent in Leishmania braziliensis. Although these two parasitic organisms belong to the same family, they are evolutionarily distantly related raising questions about the conservation of the RNAi pathway. Here we carried out an in‐depth analysis of small interfering RNAs (siRNAs) associated with L. braziliensis Argonaute1 (LbrAGO1). In contrast to T. brucei, Leishmania siRNAs are sensitive to 3′ end oxidation, indicating the absence of blocking groups, and the Leishmania genome does not code for a HEN1 RNA 2′‐O‐methyltransferase, which modifies small RNA 3′ ends. Consistent with this observation, ∼ 20% of siRNA 3′ ends carry non‐templated uridines. Thus siRNA biogenesis, and most likely their metabolism, is different in these organisms. Similarly to T. brucei, putative mobile elements and repeats constitute the major Leishmania siRNA‐producing loci and AGO1 ablation leads to accumulation of long transcripts derived from putative mobile elements. However, contrary to T. brucei, no siRNAs were detected from other genomic regions with the potential to form double‐stranded RNA, namely sites of convergent transcription and inverted repeats. Thus, our results indicate that organism‐specific diversification has occurred in the RNAi pathway during evolution of the trypanosomatid lineage.